(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the composition of the transformation operator Vekua-Erdey-Loundes with Bessel function in the nucleus and the fractional order operator Reeman-Zuivill is studied. As a result a new prevention with a degenerated hypergeometric function Gumbert in the nucleus is recieved.